New copper carboxylate pyrene dimers: synthesis, crystal structure, Hirshfeld surface analysis and electrochemical characterization - Vianca C. Nogué-Guzmán; Alejandro Burgos-Suazo; Javier O. Rivera-Reyes; Vasti P. Montes Quiñones; Paola C. Ramis-Aybar; Adriana C. Burgos-Jiménez; Karilys González-Nieves; Dalice M. Piñero-Cruz (Acta Crystallographica Section E: Crystallographic Communications, 2024)
Two new copper dimers, namely, bis(dimethyl sulfoxide)tetrakis(μ-pyrene-1-carboxylato)dicopper(Cu—Cu), [Cu2(C17H9O2)4(C2H6OS)2] or [Cu2(pyr-COO−)4(DMSO)2] (1), and bis(dimethylformamide)tetrakis(μ-pyrene-1-carboxylato)dicopper(Cu—Cu), [Cu2(C17H9O2)4(C3H7NO)2] or [Cu2(pyr-COO−)4(DMF)2] (2) (pyr = pyrene), were synthesized from the reaction of pyrene-1-carboxylic acid, copper(II) nitrate and triethylamine from solvents DMSO and DMF, respectively. While 1 crystallized in the space group P\overline{1}, the crystal structure of 2 is in space group P21/n. The Cu atoms have octahedral geometries, with four oxygen atoms from carboxylate pyrene ligands occupying the equatorial positions, a solvent molecule coordinating at one of the axial positions, and a Cu...Cu contact in the opposite position. The packing in the crystal structures exhibits π–π stacking interactions and short contacts through the solvent molecules. The Hirshfeld surfaces and two-dimensional fingerprint plots were generated for both compounds to better understand the intermolecular interactions and the contribution of heteroatoms from the solvent ligands to the crystal packing. In addition, a Cu2+/Cu1+ quasi-reversible redox process was identified for compound 2 using cyclic voltammetry that accounts for a diffusion-controlled electron-donation process to the Cu dimer.